An investigation into the constitutionality of vaccine mandates in South Africa - Thobela, Slungu Joseph (My University, 2024)
This research investigates the constitutionality of vaccine mandates in South Africa against the backdrop of the COVID-19 pandemic. Since the WHO declared COVID-19 the global pandemic in 2020, efforts have been taken to implement vaccination programmes to combat the spread of the pandemic. One of the strategies implemented to improve vaccination rates has been to make vaccinations mandatory – either directly or indirectly. This has prompted debates about the constitutionality of vaccine mandates. The vexed question is whether vaccine mandates are constitutional in South Africa. The research emphasises the need for a tenuous balance between individual human rights and public health imperatives. The Bill of Rights contains human rights such as the right to bodily integrity, human dignity, and privacy, which must be weighed against the state's duty to protect public health. The absence of legislation (law of general application) regulating vaccine mandates, as demanded by section 36 of the Constitution, raises concerns about their compliance. Limitations on the right to bodily integrity and religious freedom are conceivable under certain circumstances, allowing for the implementation of vaccine mandates. However, such limitations must align with constitutional principles, ensuring a fair, democratic, and justifiable approach. Key findings underscore that vaccine mandates, in the absence of a law of general application, may not align with the Constitution. Violations of bodily integrity and religious rights are identified, necessitating a nuanced approach to balancing individual freedoms and public health. The study concludes that any potential limitations must adhere to constitutional requirements and be implemented transparently and fairly. Methodically, the study is qualitative. It uses the content analysis of primary and secondary literature such as the Constitution, case law, books, journal articles and international instruments.
Thesis (LLM. (Development and Management)) -- University of Limpopo, 2024
Keywords: Vaccine mandates; Human rights limitations; Ethical considerations; Bodily integrity; Freedom of religion and conscience; Vaccine mandates -- South Africa; COVID-19 vaccines; Vaccination -- Law and legislation